Do people who consciously attend to their movements have more self-reported knee pain? An exploratory cross-sectional study. (January 2015) - Selfe, James; Dey, Paola; Richards, Jim; Cook, Neil; Chohan, Ambreen; Payne, Katherine; Masters, Rich
Objectives: This study explored the relationship between propensity for conscious control of movement (assessed by the Movement-Specific Reinvestment Scale) and self-reported knee pain. Design: Cross-sectional study. Setting: General population. Subjects: Adults aged 18 to 55 years of age. Measures: Participants completed the movement-specific reinvestment scale and a self-report questionnaire on knee pain at the same time on one occasion. Results: Data was collected on 101 adults of whom 34 (33.7%) self-reported knee pain. Mean scores on the conscious motor processing subscale of the movement-specific reinvestment scale, but not the movement self-consciousness subscale, were significantly higher for participants who reported knee pain within the previous year compared with those who did not (mean difference 3.03; t -test 2.66, df = 97, P = 0.009; 95% confidence interval (CI) 0.77 to 5.30). The association between self-reported knee pain and propensity for conscious motor processing was still observed, even after controlling for movement self-consciousness subscale scores, age, gender and body mass index (adjusted odds ratio 1.16, 95% CI 1.04 to 1.30). Conclusions: Propensity for conscious control of movement may play a role in knee pain.